Active noise control in three dimensional enclosure - Gong, Xuesong. (2009)
Active Noise Control (ANC) uses a secondary source to generate a sound that will cancel an undesired noise from the primary source. In this study, a single sensor ANC system is investigated. The noise field at any point in a three dimensional enclosure is modeled as a moving average process. The adaptive filtering algorithm, filtered-X LMS algorithm, is implemented to estimate characteristics of the process. These estimated characteristics are then used to predict the future values of the noise field. A canceling wave which is equal in magnitude and opposite in phase to these estimated values is generated. When the prediction is accurate, the two fields will interfere destructively and cancel each other. This approach avoids the acoustic feedback problem inherent in many multiple sensor ANC systems.